PELAKSANAAN KEWAJIBAN SUAMI TERHADAP ISTRI DALAM MASA IDDAH MENURUT HUKUM ISLAM DI DESA BATU BINTANG KEC. BATU MAR-MAR KAB. PAMEKASAN - Muhammad Kholil (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2018)
Among the wisdom of the iddah, among others, is to provide a chance to return with a clear mind, after they face a hot and so turbulent household condition that results in their marriage breaking up. In divorce because of the husband's death, the purpose of the iddah is seen in terms of its usefulness, iddah is held to show a sense of belonging to the death of the husband. Knowing whether in the period of iddah which ranges between 3 (three) or four months, the wife in a state of containing or not is an effort to respect religious values even though the reality in the village of Bangkes is not as regulated in Islamic law. As has been found in the rules of the Islamic religion that women who are in the iddah period if the iddah is thalaq qat'ie, the husband has the right to refer it back, but if he wants to marry another man then he must wait until the iddah period is up. Thalaq ba'ien husband is not entitled to refer him back except with a new marriage contract if he has expired his iddah period.